Looking to the Middle of the Qualitative-Quantitative Spectrum for Integrated Mixed Methods. (December 2021) - Paoletti, Jensine; Bisbey, Tiffany M.; Zajac, Stephanie; Waller, Mary J.; Salas, Eduardo
Substantially advancing the study of teams will require a new research paradigm complete with methods capable of capturing the complex, dynamic process of teamwork. In this paper, we suggest studying teams with an integrated mixed methods approach (i.e., methods defined by an interconnected mix of quantitative and qualitative characteristics) can help address current methodological shortcomings of our science by promoting sufficiently contextualized research. Through a review of methods, we highlight exemplars of integrated mixed methods that have the potential to be more widely adopted; namely, interaction analysis, content analysis, cluster analysis, state space grids, and agent-based modeling.